Tocilizumab combined with cyclophosphamide for the treatment of rapidly progressive refractory systemic sclerosis with predominant cardiac involvement: a case report - Fu, Zhong-Chao; Ji, Jing; Cheng, Xiao-Gui; Shi, Ran-Geng; Mo, Xiao-Feng; Yang, Zhi-Zhu (Frontiers in Immunology, 2025)
Systemic sclerosis (SSc) with multi-organ involvement poses significant therapeutic challenges. We present a case of rapidly progressive, refractory SSc with cardiac, musculoskeletal, and skin manifestations that was successfully managed with a combination of cyclophosphamide (CYC) and tocilizumab (TCZ). In this case, a 25-year-old female patient with rapidly progressive SSc developed severe skin sclerosis (mRSS 46), myofascial edema, myopathy (CK 923 U/L), joint flexion contractures, and pericardial effusion. Initial therapy with glucocorticoids and CYC showed limited efficacy. After therapeutic escalation to an alternating 4-week regimen (TCZ 8 mg/kg and CYC 600 mg administered sequentially every 2 weeks), pericardial effusion resolved completely, skin softening was observed (mRSS reduced to 32), and functional status improved significantly, with no significant adverse events reported. This case highlights the potential efficacy and safety of the CYC-TCZ combination therapy for refractory SSc, particularly in patients with cardiac involvement. These findings support the need for further exploration of this regimen in clinical trials.